It’s not just adults who gnash their teeth - a comprehensive review of the latest information on bruxism in children - Wajdowicz, Barbara; Broniec, Gabriela; Kowalska, Klaudia; Pacek, Laura; Kudła, Aleksandra; Kiełt, Weronika; Czapiewska, Rozalia; Kozłowska, Julia; Wróbel, Aleksandra; Dziewulska, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction Bruxism is a parafunction characterized by excessive chewing muscle activity involving grinding or clenching of the teeth. Bruxism has become a significant challenge in the field of pediatric dentistry. Aim of the study The aim of this comprehensive review is to provide an overview of bruxism in children, focusing on etiology, symptoms, diagnosis, and current treatment options. To draw attention to the prevalence of the disorder and to raise awareness of the importance of early recognition and intervention for bruxism in children. Materials and methods An analysis of scientific articles available in the PubMed and Google Scholar databases was conducted. Our research is supported by all relevant publications from recent years. The etiology, diagnosis, and treatment of bruxism in children were of particular interest in the study. This process involved the use of the following keywords: ‘bruxism’, ‘children’, ‘sleep bruxism’, ‘tooth wear’, ‘bruxism diagnosis’, ‘bruxism etiology’, ‘bruxism treatment’. Conclusions We evaluated 31 relevant publications. The results of the study indicate a variation in the prevalence of bruxism in children, oscillating between 13-49%. The etiology of this disorder is multidimensional and remains incompletely elucidated. The primary methods of diagnosing bruxism in younger patients include observation by parents or caregivers, a thorough health history and intraoral and extraoral dental examination. Physiotherapy and psychotherapy are recommended for the treatment of nocturnal bruxism in children. Prompt recognition of the disorder and implementation of appropriate therapy can help to halt the progression of motor dysfunction of the masticatory apparatus in children.